HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN HOMESICKNESS PADA MAHASISWA RANTAU YANG BERASAL DARI LUAR PULAU JAWA DI UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA KAMPUS PAKUWON CITY - Istanto, Trinanda Linggayuni; Engry, Agustina (Universitas Katolik Widya Mandala Surabaya, 2019)
Homesickness is a distress caused by separation from home to the new environment. Homesickness often occurs to overseas students in the first year of college and if it occurs for too long, it will cause negative impact, therefore social support is needed. Social support refers to comfort feeling that occurs through social process that can make a person reduce the negative impact caused by negative stress. This study aims to find out about relationship between social support and homesickness in first year students that came from outside Java Island at Widya Mandala Catholic University Surabaya Pakuwon City Campus. Participant in this research (N=149) is the first year students that came from outside Java Island at Widya Mandala Catholic University Surabaya Pakuwon City Campus. Sampling technique that used in this study was disproportionate stratified random sampling. This study was analyzed using non parametric correlated method Kendall’s Tau-b. Result of this study shows correlation coefficient (r) = -0,381 dan p = 0,000 (p < 0,05), it means there is significant negative correlations between social support and homesickness in first year students that came from outside Java Island at Widya Mandala Catholic University Surabaya Pakuwon City Campus